Why Do You Still Want to Buy HP Laptop? A Study of HP’S Customer Satisfaction - Rosmelia Yusof; Gan Kia Hui; Ahmad Luqman Bin Abd Samat; Aimar Ilhan Bin Abd Halim; Alsie Jocelyn Anak Andrew; Alysha Maisarah Binti Ahmad Munir; Adam Fadhlan; Adhyastar Izhar Resvara Arifin (AIBPM Publisher, 2023)
HP (Hewlett-Packard) Company was founded in July 1939 in California. This American multinational company is well known for providing electronic devices, especially laptops and computers globally. However, this research focuses on the laptop that has been produced by HP company. The purpose or objective of the study is to discover the elements that influence consumer satisfaction towards HP laptops. The research's primary goals are to evaluate the amount of customer satisfaction with HP laptops. The researchers provide survey questionnaires via google form to collect the Primary data, and the researchers also refer to the relevant articles, journals, and other material to find secondary data. The results show that Relationship marketing and Price Satisfaction have a significant positive relationship with customer satisfaction. Those lead Relationship Marketing and Price Satisfaction of HP will increase customer satisfaction.